Micro-Entrepreneurship and Subjective Well-Being: Evidence from Rural Bangladesh - Muhammad Faress Bhuiyan; Artjoms Ivlevs (Institute of Labor Economics (IZA), 2018)
Microcredit has long been hailed as a powerful tool to promote livelihoods and reduce poverty through entrepreneurship. However, its impacts on people's subjective well-being remain underexplored. We present a unified theoretical framework for analyzing the effect of microcredit-enabled entrepreneurship on overall life satisfaction â exteuro“ a key manifestation of subjective well-being. Empirically, we apply an instrumental variable approach to a unique census-like household survey conducted in three villages of Bangladesh in 2013. In spite of having no direct effects, we find that microcredit borrowing has an indirect negative effect on overall life satisfaction, through increased worry. On a positive note, we find that female micro-borrowers experience an increase in satisfaction with financial security and achievement in life. We also provide evidence that micro-borrowers with higher levels of assets experience an increase in satisfaction with financial security.
Keywords: I31; J16; L26; 330; depression; happiness; life satisfaction; entrepreneurship; microcredit; worry; female empowerment; Bangladesh